Theme-rheme analysis of the Jakarta post headlines on covid-19 issue - Angelin Tandi Kalotong (Politeknik Negeri Bali, 2020)
COVID-19 has been impacted worldwide attention since it is a serious disease. Millions of people are infected and the aspects of the government have been descent. COVID-19 has become a daily topic for Indonesia’s newspapers. Media has an important role in giving information and awareness about this issue. Critical Discourse Analysis performs in portraying this issue by figuring out the representation of COVID-19 in the headlines. The headlines on The Jakarta Post were analyzed by employing Halliday’s Systemic Functional Linguistic. The data were taken by observing twenty newspaper headlines from The Jakarta Post newspaper on the national column on the first-week edition using purposive sampling. The writer uses purposive sampling because the writer wants to determine the sampling by specifying special characteristics. The newspaper uses a topical theme in all of the headlines, yet the participants of the Theme are different. The participants involved in the headlines were Actor, Verbiage, Sayer, Senser, and Goal as their Themes. In representing the COVID-19, The Jakarta Post newspaper headlines used the Theme to figure out the participant of the headlines. The participant Actor shows the action or the content of the headlines. Participant Verbiage shows the content of the headline. Participant Sayer directly says the content of the headline. Participant Senser shows that people are suffered due to this virus. Participant Goal shows that the action gives a positive impact on something related to the topic. The Jakarta Post newspaper uses these themes in order to examine the representations of COVID-19 in Indonesia that is a dangerous virus. The dangers of COVID-19 can be seen by the use of the participant Actor that is mostly done by the government.